2023
DOI: 10.1002/iub.2725
|View full text |Cite
|
Sign up to set email alerts
|

Amitriptyline efficacy in decreasing implant‐induced foreign body reaction

Abstract: Beyond its actions on the nervous system, amitriptyline (AM) has been shown to lower inflammatory, angiogenic, and fibrogenic markers in a few pathological conditions in human and in experimental animal models. However, its effects on foreign body reaction (FBR), a complex adverse healing process, after biomedical material implantation are not known. We have evaluated the effects of AM on the angiogenic and fibrogenic components on a model of implant‐induced FBR. Sponge disks were implanted subcutaneously in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Previous studies had indicated that the fibrotic capsule around the implants can lead to devices failure and mechanical impairment. 37,38 The formation of the capsule is influenced by several factors, including properties of the implants, surface texture, and implantation site. 27,39 Our descriptive histologic analysis showed thinner fibrotic capsule around implants in omental group when compared with capsule in control group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had indicated that the fibrotic capsule around the implants can lead to devices failure and mechanical impairment. 37,38 The formation of the capsule is influenced by several factors, including properties of the implants, surface texture, and implantation site. 27,39 Our descriptive histologic analysis showed thinner fibrotic capsule around implants in omental group when compared with capsule in control group.…”
Section: Discussionmentioning
confidence: 99%